Antibody to Herpesvirus hominis in Patients with Carcinoma of the Cervix - Najem, S. N. (1982)
An ELISA test was used to measure the levels of antibody to Herpesvirus hominis in a group of women with carcinoma of the cervix. The results were compared to those in a similar group of age-matched controls. The mean titre of antibody in the patients with carcinoma of the cervix was significantly greater than in the corresponding control group using both HSV-1 and HSV-2 antigens.